Fitness Level‐ and Sex-Related Differences in Macrovascular and Microvascular Responses during Reactive Hyperemia. Issue 3 (March 2022) - RASICA, LETIZIA; INGLIS, ERIN CALAINE; IANNETTA, DANILO; SOARES, ROGERIO N.; MURIAS, JUAN M.
ABSTRACT: Purpose: Reactive hyperemia (RH) is widely used for the investigation of macrovascular (flow-mediated dilation, or FMD) and microvascular (near-infrared spectroscopy–vascular occlusion test, or NIRS-VOT) function. Mixed results have been reported on fitness level‐ and sex-related differences in FMD outcomes, and little is known about microvascular differences in untrained and chronically trained males and females. Methods: Fifteen chronically trained (CT: 8 males, 7 females) and 16 untrained (UT: 8 males, 8 females) individuals participated in this study. Aerobic fitness (V˙O2max ) was assessed during a cycling incremental exercise test to volitional exhaustion. FMD and NIRS-VOT were performed simultaneously on the lower limb investigating superficial femoral artery and vastus lateralis muscle, respectively. Results: %FMD was not different between groups (CT males, 4.62 ± 1.42; CT females, 4.15 ± 2.23; UT males, 5.10 ± 2.53; CT females, 3.20 ± 1.67). Peak blood flow showed greater values in CT versus UT ( P ⩽ 0.0001) and males versus females ( P = 0.032). RH blood flow area under the curve was greater in CT versus UT ( P = 0.001). At the microvascular level, desaturation and reperfusion rates were faster in CT versus UT ( P = 0.018 and P = 0.013) and males versus females ( P = 0.011 and P = 0.005). V˙O2max was significantly correlated with reperfusion rate ( P = 0.0005) but not with %FMD. Conclusions: Whereas NIRS-VOT outcomes identified fitness- and sex-related differences in vascular responses, %FMD did not. However, when RH-related outcomes from the FMD analysis were considered, fitness- and/or sex-related differences were detected. These data highlight the importance of integrating FMD and NIRS-VOT outcomes for a more comprehensive evaluation of vascular function.